Effectiveness of the System of Addictology Services in The Czech Republic in Context of the COVID-19 Pandemic – Initial Analysis - Radek SOBĚHART; Michael FANTA; Aleš ROD; Barbora ORLÍKOVÁ (Communications of International Proceedings, 2021)
The paper is aimed at initial analysis of the system of addictology services in the Czech Republic. It defines its fundamental socio-economic parameters that impact the so-called addictive behavior (unemployment, education level, level of indebtedness, income, and stable housing). The paper also discusses several key changes in connection with the ongoing COVID-19 pandemic that primarily impacts the access to addictology services and their financing. The objective of the paper is to introduce the international scientific public to the fundaments of addictology services in the Czech Republic and to identify the services’ main system-wide deficits.
Keywords: Public Policy; Addictology; Czech Republic; Covid-19 Pandemic